2006
DOI: 10.1121/1.2258438
|View full text |Cite
|
Sign up to set email alerts
|

The use of microperforated plates to attenuate cavity resonances

Abstract: The use of microperforated plates to introduce damping in a closed cavity is examined. By placing a microperforated plate well inside the cavity instead of near a wall as traditionally done in room acoustics, high attenuation can be obtained for specific acoustic modes, compared with the lower attenuation that can be obtained in a broad frequency range with the conventional position of the plate. An analytical method for predicting the attenuation is presented. The method involves finding complex eigenvalues a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…The proposed PTF approach is used to investigate the acoustic field inside a rectangular cavity used in Fenech et al 15 Results obtained from the present approach are compared with the experimental data reported in that paper. This comparison allows further validation of the proposed approach in a more complex vibro-acoustic environment.…”
Section: Experimental Validationsmentioning
confidence: 72%
See 3 more Smart Citations
“…The proposed PTF approach is used to investigate the acoustic field inside a rectangular cavity used in Fenech et al 15 Results obtained from the present approach are compared with the experimental data reported in that paper. This comparison allows further validation of the proposed approach in a more complex vibro-acoustic environment.…”
Section: Experimental Validationsmentioning
confidence: 72%
“…9). In Fenech et al 15 the reverberation time of the empty cavity was found to be $0.5 s in most of the frequency range of interest. This allows the estimation of an overall damping loss factor from g ¼ 2:2=fT r , where f is the frequency and T r the reverberation time.…”
Section: Experimental Validationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In some works [Fenech et al, 2006;Liu and Herrin, 2010;Yang et al, 2015], the use of micro-perforated panels (MPP) are proposed, which are based on the fundamentals of HR. In this case, each perforation effectively represents a resonator with the backing air cavity representing the expansion chamber of a conventional resonator [Arenas and Crocker, 2010].…”
Section: Helmholtz Resonatormentioning
confidence: 99%